Hsp90 as a pathophysiological factor and emerging therapeutic target in atopic dermatitis - Tukaj, Stefan (Frontiers in Immunology, 2025)
Heat shock protein 90 (Hsp90) is a molecular chaperone that plays a critical role in stabilizing and regulating numerous client proteins involved in inflammation, immune activation, and skin barrier homeostasis. Emerging evidence suggests that Hsp90 contributes to the pathophysiology of atopic dermatitis (AD), a chronic inflammatory skin disorder characterized by immune dysregulation, epidermal barrier dysfunction, and microbial imbalance. Notably, elevated intracellular Hsp90 activity has been reported in peripheral blood leukocytes of AD patients, alongside increased extracellular Hsp90 and anti-Hsp90 IgE antibodies. Preclinical studies employing murine models of AD, including dinitrochlorobenzene (DNCB)- and calcipotriol (MC903)-induced dermatitis, have demonstrated that both topical and systemic inhibition of Hsp90 ameliorates disease severity. These improvements correlate with reduced epidermal hyperplasia, decreased expression of Th/Th2 cytokines, attenuation of keratinocyte-derived alarmins, and suppression of inflammation. Additionally, Hsp90 inhibition limits the infiltration or activation of immune cells such as T cells, neutrophils, eosinophiles, and mast cells in the skin. Mechanistic investigations reveal that Hsp90 blockade downregulates key signaling pathways implicated in AD pathogenesis, notably NF-κB and JAK-STAT. In vitro studies further corroborate that Hsp90 inhibition reduces proinflammatory responses in keratinocytes, CD4+ T cells, and eosinophils. Beyond modulating skin inflammation, Hsp90 blockade partially restores gut microbiota dysbiosis and impairs Staphylococcus aureus biofilm formation, both relevant to AD pathogenesis. Although clinical data on Hsp90 inhibitors in AD are still lacking, early-phase trials in psoriasis and hidradenitis suppurativa suggest potential therapeutic benefit. Collectively, these findings underscore a multifaceted role for Hsp90 in AD and support its potential as a promising novel therapeutic target.